Minimally invasive pancreatic resections: cost and value perspectives. Issue 3 (March 2017) - ,; Asbun, Horacio J.; Barkun, Jeffrey; Besselink, Marc G.H.; Boggi, Ugo; Conlon, Kevin C.P.; Han, Ho-Seong; Hansen, Paul D.; Kendrick, Michael L.; Kooby, David A.; Montagnini, Andre L.; Palanivelu, C.; et al.
Abstract: Background: The number of minimally invasive pancreatic resections (MIPR) performed for benign or malignant disease, have increased in recent years. However, there is limited information regarding cost/value implications. Methods: An international conference evaluating MIPR was held during the 12th Bi-Annual International Hepato-Pancreato-Biliary Association (IHPBA) World Congress in Sao Paulo, Brazil, on April 20th, 2016. This manuscript summarizes the presentations that reviewed current topics in cost and value as they pertain to MIPR. Results: Compared to the open approach, MIPR's are associated with higher operative costs but lower postoperative costs. However, measurements of patient value (defined as improvement in both quantity and quality of life) and financial value (using incremental cost-effectiveness ratio) are required to determine the true value at societal level. Conclusion: Challenges remain as to how the potential benefits, both to the patient and the healthcare system as a whole, are measured. Research comparing MIPR versus other techniques for pancreatectomy will require appropriate and valid measurement tools, some of which are yet to be refined. Nonetheless, the experience to date would support the continued development of MIPR by experienced surgeons in high-volume pancreatic centers, married with appropriate review and recalibration.